FAKTOR YANG MEMPENGARUHI HARGA SAHAM PADA PERUSAHAAN PERBANKAN DI INDONESIA (Students' Journal of Accounting and Banking, 2012)
The purpose of this research is to emperically study factors that affect stock prices in perbankkan company listed on the stock exchange Indonesia. Population of this research are go public firms on Indonesia Stock Exchange (ISX) during the periode of 2008 to 2010.The samples are obtained by using purposive sampling method. The statistic method being used is multiple linear regression with the model being tested previously in classic assumptions.The result indicate that partially loan to deposit, return on equity and earning per share variable has significantly influenced the stock price, and partially capital adequacy ratio and non-performing loan has no sigificant influenced the stock price.Keywords: Capital Adequacy Ratio, Loan To Deposite Ratio, Non-Performing Loan, Return On Equity, Earning Per Share, Stock Price